Testing the environmental Kuznets curve with structural breaks: the role of globalization, energy use, and regulatory quality in South Africa - Gungor, Hasan; Abu-Goodman, Maryam; Olanipekun, Ifedolapo Olabisi; Usman, Ojonugwa (Springer Heidelberg, 2021)
This study uncovers the role of regulatory quality, energy use, and globalization in the conventional environmental Kuznets curve (EKC) for South Africa by incorporating structural breaks in the series based on quarterly frequency data between 1996:Q1 and 2016:Q4. Applying the autoregressive distributed lag (ARDL) model, we confirm a cointegration between the variables. The empirical results suggest the validity of the EKC hypothesis in South Africa. In addition, while energy use exerts positive pressure on ecological footprint, globalization and regulatory quality exert negative pressure on ecological footprint. However, the effect of globalization is weak in the long run while the effect of regulatory quality is weak in short run. The results further reveal that the structural break years are statistically insignificant. The causality result establishes a causal link flowing from all the variables to ecological footprint in the long run. In the short run, economic growth and energy use Granger-cause regulatory quality. Also, while energy use causes ecological footprint, globalization is a predictor of energy use. The policy implication of this study is that increasing the pace of globalization and strengthening regulatory quality are efficient strategies to improve environmental quality and sustain a stable EKC in South Africa.
Keywords: Globalization; Energy consumption; Regulatory quality; Ecological footprint; ARDL model